2023
DOI: 10.1159/000530873
|View full text |Cite
|
Sign up to set email alerts
|

Timing of Initiation of Acute Stroke Rehabilitation and Management Corresponding to Complications at Primary Stroke Centers in Japan: A Nationwide Cross-Sectional Web-Based Questionnaire Survey

Abstract: <b><i>Introduction:</i></b> Many guidelines now recommend early rehabilitation for acute stroke patients. However, evidence remains lacking regarding the specific timings for initiation of various rehabilitation steps and management when complications are encountered in acute stroke rehabilitation. This survey aimed to investigate actual clinical situations in acute stroke rehabilitation in Japan and to improve the medical systems for rehabilitation and plan further studies. <b>&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…In patients with subarachnoid hemorrhage (after ruptured aneurysm treatment), the training tended to start later. 12) These findings indicate that starting in-bed ROM training early after onset does not result in an increase in adverse events and may improve functional outcome, although further evidence is required.…”
Section: Commentarymentioning
confidence: 79%
See 4 more Smart Citations
“…In patients with subarachnoid hemorrhage (after ruptured aneurysm treatment), the training tended to start later. 12) These findings indicate that starting in-bed ROM training early after onset does not result in an increase in adverse events and may improve functional outcome, although further evidence is required.…”
Section: Commentarymentioning
confidence: 79%
“…29) A questionnaire survey on acute stroke rehabilitation conducted in Japan in 2022 showed that the greatest number of facilities started mobility training (sitting, transferring, standing, and walking) in branch atheromatous disease, atherothrombotic brain infarction, and cardioembolic stroke on hospitalization day 2, followed in descending order of frequency by hospitalization day 3 and the day of admission. 12) In patients with lacunar infarctions, the timing of starting mobilization was earlier than in other types, with approximately the same proportion of facilities (slightly more than 40%) starting mobilization on the day of admission and on hospitalization day 2. 12) As indicated above, if one were to suggest the appropriate timing for mobilization, at present it would likely be considered between 24 and 48 h. Very early mobilization within 24 h of onset may be considered for patients with mild symptoms or those with non-elderly ischemic stroke provided that mobilization time is shortened and its frequency is increased.…”
Section: Commentarymentioning
confidence: 93%
See 3 more Smart Citations